2011
DOI: 10.1007/s12041-011-0086-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypermutation and stress adaptation in bacteria

Abstract: Hypermutability is a phenotype characterized by a moderate to high elevation of spontaneous mutation rates and could result from DNA replication errors, defects in error correction mechanisms and many other causes. The elevated mutation rates are helpful to organisms to adapt to sudden and unforeseen threats to survival. At the same time hypermutability also leads to the generation of many deleterious mutations which offset its adaptive value and therefore disadvantageous. Nevertheless, it is very common in na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 106 publications
(127 reference statements)
1
15
0
Order By: Relevance
“…This suggests that they may evolve the same type of stress mechanism and DNA repair. However, all the treatments originate from the same bacterial clone, suggesting that the initial stress adaptation may involve mutation as it has been suggested that hypermutation is a feature in initial stress adaptations [54]. …”
Section: Discussionmentioning
confidence: 99%
“…This suggests that they may evolve the same type of stress mechanism and DNA repair. However, all the treatments originate from the same bacterial clone, suggesting that the initial stress adaptation may involve mutation as it has been suggested that hypermutation is a feature in initial stress adaptations [54]. …”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was also analyzed in the present study. The repeat isolates are often much more virulent and more likely to be MDR [20,21]. Because obtaining repeat isolates is specifically related to hospital environments and therapy, a risk analysis was performed on these isolates for resistance to imipenem and meropenem.…”
Section: Introductionmentioning
confidence: 99%
“…Strains with high mutation rates are selected only because of them have a greater possibility of acquiring adaptive mutations in genes unrelated with the hyper-mutable phenotype (second-order selection) [22]. We might consider if the emergence of normo-mutable variants within a population of mutators is also of a similar indirect type, as these variants are similarly selected by the association with favorable traits.…”
Section: Introductionmentioning
confidence: 99%